Modal Intelektual Pustakawan dalam Penyebaran Informasi di Perpustakaan Sekolah Dasar - Nuristia, Maghfira; Laksmi, Laksmi (Tik Ilmeu : Jurnal Ilmu Perpustakaan dan Informasi, 2023)
Intellectual capital has a role in disseminating information in libraries, this is because the process of disseminating information cannot only rely on library materials. The wider the intellectual capital owned, the more information that can be disseminated. Intellectual capital consists of human capital, structural capital, and relational capital. The librarian is the actor who disseminates information in the Elementary School Library, the information that is disseminated should be correct and can be accounted for. This study aims to identify the role of intellectual capital for librarians in disclosing information in elementary school libraries. This study uses a qualitative method with a case study approach. Selection of informants using purposive sampling technique. Data collection methods in this study were interviews and observation. The results showed that librarians' intellectual capital consisting of human capital, structural capital, and relational capital played a role in disseminating information in the SDIA 61 library. Human capital played a role in the information assistance process, structural capital played a role in the process of preparing information, and relational capital played a role in therapeutic techniques information and the type of information disseminated